Shear Strength between Cemented Paste Backfill - Koupouli, Jean-Frédéric N.; Belem, T.; Rivard, P. (Algerian Journal of Research and Technology (AJRT), 2019)
After placement underground, the physical–chemical and mechanical properties of unsaturated cemented paste backfill (CPB) will evolve over time due to self-weight consolidation and binder hydration. However, the behavior of the interface CPB-rock wall is not well known. This paper attempt to bring experimental results in order to better understand this behavior. The rock interface replicas were made from natural rock surfaces (schist and granite). Both frictional shear and shear bond strengths were determined. The results show that the shear strength at the schist interface (rougher) is higher than the one at the granite interface. The cohesion and the interfacial friction angle depend on the CPB curing time (hydration) and the applied normal stress.